The spectrum of histomorphological features in psoriasis: a three years study - Dr. Deepti Arora; Dr. Ankita Mittal; Dr. Faiyaz Ahmad; Dr. Shyamoli Dutta; Dr. Seema Awasthi, Seema (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: Psoriasis is a common relapsing chronic inflammatory dermatological disease associated with significant morbidity. Psoriasis is the prototype of a group of cutaneous disorders (psoriasiform dermatitides). Although histopathology is considered ‘gold standard’ for the diagnosis of psoriasis, at times even histopathological findings are confusing and inconclusive. Aim of the study: To study the histopathological findings at different stages of psoriasis and its subtypes. Materials and Methods: A total of 101 cases were studied for histopathological features. Results: Most of the cases were noted in the age group of 31 to 40 years (25.9%). There was a male predominance with male to female ratio of 2.7:1. Psoriasis vulgaris was the most common clinical type followed by Palmoplantar psoriasisand Erythrodermic psoriasis. Parakeratosis was the only consistent feature followed by ddilated blood vessels/abnormal capillary pattern and elongation of rete ridges with thickening at lower ends. The other frequent features were acanthosis and agranulosis / hypogranulosis. Conclusion: Histopathology of psoriatic plaques exhibits heterogeneity and microscopic features will vary according to the stage of the disease. Though most of the predominant morphologic features of psoriasis are related to the epidermis, the presence of dilated blood vessels and/or abnormal capillary pattern is a constant finding in all stages of psoriasis and thus, can help in diagnosis of psoriatic lesion when in doubt.